COPYRIGHT REGISTRATION ACCOMPANIMENT FOR THE SONG "KANWIL KEMENKUMHAM KEPRI MENUJU WILAYAH BEBAS KORUPSI" CREATED BY MR. ERICK JUNATA - Regent Regent; Febri Jaya (ConCEPt - Conference on Community Engagement Project, 2022)
Intellectual property is the result of human thought in which there are moral rights and economic rights that are specifically attached to the creator and are protected by the state as part of human rights. Intellectual property registration is a process carried out to obtain a creation registration letter as part of the legal protection effort for the rights of the creator. However, this intellectual property registration process is a separate problem for the creators because in its implementation it is considered to still cause various obstacles. This community service program aims to provide facilities and educational facilities for the community in the intellectual property registration process for their work. The method of implementing this community service activity is to use the partner data collection method, discuss the details of the copyright registration fee with partners, and register the copyright for the partner's song.